Exploring Associations Between Inner-Context Factors and Implementation Outcomes. (January 2020) - Suhrheinrich, Jessica; Rieth, Sarah R.; Dickson, Kelsey S.; Stahmer, Aubyn C.
Classroom pivotal response teaching (CPRT) is an evidence-based practice (EBP) adapted for classroom use. A recent effectiveness trial of CPRT involved training 98 special education classrooms in Southern California. The Exploration, Planning, Implementation, and Sustainment (EPIS) conceptual framework illustrates the impact of inner- and outer-context factors on implementation outcomes. This article evaluates how teacher factors (including attitudes toward EBP) and organizational factors (implementation climate and district support) influence training outcomes (fidelity of intervention, report of use, sustainment, and satisfaction). Teachers' ratings of training quality were related to higher fidelity during their follow-up year, β = .34, t (78) = 2.97, p < .004, and rating of intervention ease of use was related to higher daily CPRT use. Teacher ratings on the appeal scale of the attitudes measure were associated with individual sustainment, β = .35, t (55) = 2.76, p < .01. Leader involvement at recruitment meetings, β = .35, t (48) = 2.58, p = .01, and provision of CPRT training space, β = .44, t (48) = 2.73, p < .01, were significantly related to school sustainment. Teachers' overall attitudes toward the intervention were significantly related to satisfaction with CPRT training, β = .41, t (80) = 3.96, p < .01. This study makes important preliminary contributions to understanding the impact of inner-context implementation determinants of a classroom-based EBP for students with autism spectrum disorder.